Utilizing Cell-Free Urinary and Plasma Tumor DNA to Predict Pathologic Stage at Radical Cystectomy - Prithvi B. Murthy; Billie Gould; Facundo Davaro; Pan Du; Lucia Camperlengo; Shreyas Naidu; Kyle Rose; Scott M. Gilbert; Philippe E. Spiess; Wade Sexton; G. Daniel Grass; Rohit Jain; et al. (Société Internationale d’Urologie Journal)
ObjectiveTo assess the ability of cell-free urinary and plasma tumor DNA (cfDNA) to predict pathologic stage at radical cystectomy for patients with clinical muscle-invasive bladder cancer. MethodsA total of 25 patients with clinical muscle-invasive bladder cancer were enrolled before undergoing radical cystectomy. Blood and urine were collected before surgery. The 600-gene PredicineATLAS panel was used to sequence blood buffy-coat germline DNA, plasma cfDNA, and urine cfDNA samples. Low-pass whole genome sequencing was performed on plasma- and urine-derived cfDNA. CfDNA tumor fraction (TF), genome-wide copy number burden (CNB), and estimated tumor mutational burden (TMB) were measured in both plasma and urine samples and their correlation with pathologic T-stage was examined. ResultsThree of 25 plasma samples had insufficient cfDNA. In 22 of 22 plasma samples and 24 of 25 urine samples, at least one nonsynonymous somatic variant was detected. Across the cohort, 44% of plasma variants were concordant with paired urine variants. The mean number of variants did not differ between noninvasive (< pT1/pN0) and invasive disease (≥ pT1 or N+) for both plasma (8 vs. 9.5 variants; P = 0.85) and urine (33.7 vs. 30 variants; P = 0.45). A strong correlation was observed between urine TF and urine CNB score within patients (rv = 0.92). Plasma TF (r = 0.38), urine TF (r = 0.21), and urine CNB score (r = 0.16) exhibited positive correlations with pT stage. Patients with carcinoma in situ (CIS) had higher mean urine TF and CNB scores ( P = 0.07 and P = 0.05, respectively). Plasma TF and CNB score did not correlate with the presence of CIS. ConclusionsCombining plasma- and urine-based cfDNA analysis may help identify patients with residual disease at radical, although we were unable to predict pathologic T-stage based on these metrics.The presence of CIS may contribute to greater urinary CNB and TF levels. Considering CIS in the analysis may improve the ability to correlate tumor metrics with pathologic stage. Low-pass whole genome sequencing–derived urinary CNB correlates strongly with urinary TF and may provide a less resource-intensive method for future longitudinal disease monitoring.